”The most important subject that can possibly be”. A response to E.A.J. Honigmann’s article - Hildegard Hammerschmidt-Hummel (Przestrzenie Teorii)
This text is a reply to E.A.J. Honigmann and presents another point of view on Shakespeare’s Catholicism. H. Hammerschmidt-Hummel defends her thesis and tries to convince that her book is based on reliable studies and historical sources. She proves that a secret Catholic code in his plays is the most important key to understanding his whole output. Her arguments are based on two evidences: the known or presumed “Catholic sympathies” of the dramatist’s family, friends and patrons and the “Catholic attitudes” embedded in the plays.